Risk Compensation and Market Returns: The Role of Investor Sentiment in the Stock Market. Issue 3 (19th February 2019) - He, Zhifang; He, Linjie; Wen, Fenghua
ABSTRACT: We investigate the effect of investor risk compensation (IRC) on stock market returns and the role of investor sentiment in influencing the link between IRC and stock returns. Results reveal that current IRC has a significant and positive effect on stock returns while past IRC has a negative effect. Meanwhile, the positive effect of current risk compensation on stock returns is sustainable with different current sentiment states, while this effect is not associated with the current magnitude of sentiment. Regarding past risk compensation, its negative impact on stock return also exists with different signs of past investor sentiment while this effect is not related to the value of past investor sentiment. We discuss the implications of the findings.